LIG4 and RAD52 DNA repair genes polymorphisms and systemic lupus erythematosus. - De Azevêdo Silva, Jaqueline; Pancotto, João Alexandre Trés; Donadi, Eduardo Antônio; Crovella, Sergio; Sandrin-Garcia, Paula (Mol Biol Rep, 2014)
Systemic lupus erythematosus (SLE) is a complex autoimmune disorder with a strong genetic background. Nevertheless, SLE might also be triggered due to environmental factors, such as UV light exposure. DNA double strand breaks (DSBs) may be induced secondarily by UV radiation, increasing DNA immunogenicity and in SLE patients DNA repair is diminished, allowing the accumulation of DSBs and genomic instability. LIG4 and RAD52 genes play important roles in DNA repair mechanisms and a recent microarray analysis showed their differential expression in active SLE patients. In this study we investigated a potential association between LIG4 and RAD52 single nucleotide polymorphisms (SNPs) and SLE predisposition in a Southeast Brazilian population. We assessed four Tag SNPs in LIG4 and three in RAD52 gene region, encompassing most of the gene sequence, in 158 SLE patients and 212 healthy controls. We also performed SNPs analysis considering clinical manifestation, gender and ethnicity in SLE patients. Our data did not show association between LIG4 and RAD52 SNPs and SLE, its clinical manifestations or ethnicity in the tested population. The analysis regarding ethnicity and SLE clinical manifestations indicated Caucasian-derived patients as more susceptible to cutaneous and hematological alterations than the African-derived. To our knowledge, this is the first association study involving LIG4 and RAD52 genes and SLE predisposition.
Keywords: Adult; Alleles; Brazil; Case-Control Studies; DNA Ligases; DNA Repair; Ethnic Groups; Female; Genetic Linkage; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Lupus Erythematosus, Systemic; Male; Middle Aged; Odds Ratio; Polymorphism, Single Nucleotide; Rad52 DNA Repair and Recombination Protein